Biochemical Study of Oxidative Stress and its Role in Recurrent Pregnancy Loss - Jaber, Hiba khalid; Hayder L.F., Al-Msaid (Journal of Science in Medicine and Life, 2025)
Background: Abortion is considered one of the important medical and social problems in the life of the couple in particular and society in general. In addition to the health risks it causes to the woman, it causes psychological, economic and family problems for the aborted women, and it is one of the factors affecting women of childbearing age. This study aimed to evaluate key biochemical and immunological markers in - Identify some of the causes of recurrent miscarriage in women The link between reactive stress and having multiple miscarriages. Ways: Ninety samples were put through a metabolic test. The amount of total reactive oxygen species in the blood was found using an ELISA reader from Germany and an immune method called Enzyme-Linked Immuno-Sorbent Assay. Before they are used, all materials and chemicals must be brought to room temperature. The chemistry tests were done in the Biology Department's labs at the University of Kufa's Faculty of Sciences. Results: The results show that abortion women are of different ages, as shown in Figure (1). There are 4 abortion women younger than 20 years, 32 abortion women younger than 30 years, and 24 abortion women younger than 40 years. There was a significant rise (p<0.05) in the level of reactive oxygen species in patients (3.285 ± 0.1225) compared to the control group (1.155±0.09705). There were no significant differences (p<0.05) in the levels of reactive oxygen species in abortion women based on their age. less than 20 years (3.328±0.3904), less than 30 years (3.168±0.1756), and less than 40 years (3.433±0.1895). Reactive oxygen species (ROS) levels were much higher in the women who had miscarriages than in the control group. This suggests that oxidative stress may play a part in the biology of miscarriage. However, ROS levels were not significantly different between women of different ages.